Children, investments in education and poverty in Malawi - Mussa, Richard (School of Economics, 2014)
This thesis presents an examination of three interrelated themes concerning household investments in the education of children, and how the number of children in a household affects a household's poverty situation in Malawi. These themes cover three chapters. Chapter 2, investigates two issues regarding household expenditure on primary educa- tion of own children using the Second Malawi Integrated Household Survey (IHS2) data. Firstly, we look at factors which influence a household's decision to spend or not (the par- ticipation decision), and by how much (the expenditure decision). This is done for urban and rural households. We found that there are differences in the factors which influence both decision levels for the two groups of households. Secondly, to get a deeper under- standing of these rural-urban spending differences, the study develops the Blinder-Oaxaca decomposition technique for the independent Double Hurdle model. The proposed decom- position is done at the aggregate and disaggregated levels. The aggregated decomposition allows us to isolate the expenditure differences into a part attributable to differences in characteristics and a part which is due to differences in coefficients. The detailed (dis-aggregated) decomposition enables us to pinpoint the major factors behind the spending gap. At the aggregate decomposition level, our results show that at least 66% of the expenditure differential is explained by differences in characteristics between rural and ur- ban households, implying that an equalization of household characteristics would lead to about 66% of the spending gap disappearing. At the disaggregated decomposition level, the rural-urban difference in household income is found to be the largest contributor to the spending gap, followed by quality of access of primary schools. Besides, rural-urban differences in mothers education and employment are found to contribute more to the spending differential relative to the same for fathers. Recognizing that in many African countries parents are not just responsible for the educa- tion of their own children, Chapter 3 examines the relationship between household income and schooling costs in the presence of intrahousehold schooling bias against non-biological children. To this end, we construct a two-period model of intrahousehold schooling bias. The model predicts that there is an asymmetry in the impact of changes in costs and income on schooling in the sense that the impact is larger for the non-biological child. It predicts that the asymmetry increases as the relationship distance between the non- v vi ABSTRACT biological child and the parents gets wider. It also shows that an increase in cost of schooling leads to a bigger reduction in schooling for poor households, and that the dif- ference in the impact of cost changes between the biological and the non-biological child declines as household income increases i.e. there is convergence. The convergence is faster the more distantly related to the parents the non-biological child is. An empirical investi- gation of these predictions using IHS2 data, shows that when current enrolment and grade attainment are used to measure schooling, the price and income elasticities of schooling are larger for non-biological children. The results also indicate that households in the low- est income quintile (the poorest) have the largest price elasticities, and households in the highest income quintile (the wealthiest) have the smallest price elasticities. We also found that the price elasticities for biological and non-biological children converge as we move from the lowest income quintile to the highest income quintile, and that the convergence is faster for non-biological children who are non-relatives. Having looked at among other things the role of household economic status on the edu- cation investments of children in Malawi in Chapters 2 and 3, in Chapter 4 we turn the question on its head and investigate the impact of fertility (number of children) on poverty in rural Malawi. We use two measures of poverty; the objective and the subjective. After accounting for endogeneity of fertility by using son preference as an instrumental variable, we found that fertility increases the probability of being objectively poor. This effect is robust for all poverty lines used. It is also robust to accounting for economies of scale and household composition as well as assuming that poverty is continuous. We also found that when fertility is treated as an exogenous variable its impact is underestimated. When poverty is measured subjectively, the results are opposite to those of objective poverty. We found that fertility lowers the likelihood of feeling poor, and that fertility is exogenous with respect to subjective poverty.